Tracing Practice-Led Research to Locate a 'Nature' in Remembering Babylon. (December 2015) - Archer-Lean, Clare; Crew, Gary
Abstract : David Malouf's novel Remembering Babylon did not, like Athena, spring fully formed from the head of Zeus. It is equally doubtful that the novel was inspired by some mystic muse. Malouf seems to have employed the scholarly methodology of practice-led research to write Remembering Babylon, gathering information from historical and literary sources, selecting and rejecting specific elements from these sources, then subjecting what he had chosen to his creative imagination. In the afterword, Malouf acknowledges the historical Gemmy Morrell's name and his actual words as the 'seed of this fiction' but 'otherwise this novel has no origin in fact.' This article will investigate specific citations included by the author and reflect on their relationship to imaginings of 'nature.' The selections will be chosen because of their particular resonance with the human–nature relationship. While the post-colonial implications of the novel are well established, the exploration of the unusual citation inclusions and exclusions extends understanding of another preoccupation within the work's creative construction: an explicit focus on human relationships with the natural world. The attitude to nature in Remembering Babylon can be read eco-critically as establishing the impossibility of eco-poiesis, enacting Kate Rigby's notion that the literary text can 'save the earth by disclosing the non-equation of the word and thing, poem and place'. In this sense, Remembering Babylon is a transcendent act of eco-critical world-making, not because it reflects the natural world in mimetic veracity, but because it represents moments of the natural world as beyond language and creates brief moments of human collapse into, and synthesis with, nature.